Layanan Bimbingan Karir Dalam Meningkatkan Perencanaan Karir - Marneva Nailul Amni Neva; Irman Irman (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
This study aims to improve students' career planningÂ class X at Madrasah Aliyah (MA) Plus An Nahl Kabupaten Lima Puluh Kota through the Career Guidance Service. Based on the results of observations made by researchers before providing services in these classes there are still many students who do not have career plans. Based on the data obtained, the researcher conducted an action research that refers to career guidance service activities. The reason the researcher will provide career guidance service action is because the counseling teacher does not carry out the service and considers this service necessary to be provided to service participants. This activity is monitored using a checklist. From the results of the research carried out, there were several indicators that experienced an increase in the